The Effect of the Numbered Heads Together Cooperative Learning Model on Students’ Learning Outcomes in Procedural Texts - Heri Anggraini; Asri Yulianda; Muhammad Rusli (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study was conducted to address the low learning outcomes of students in writing procedural texts, which are often caused using conventional and less engaging teaching methods. To overcome this issue, the Numbered Heads Together (NHT) cooperative learning model was implemented as a more interactive and collaborative alternative. The purpose of this study was to determine the effect of the NHT model on students’ learning outcomes in writing procedural texts for Grade VII students at MTs Al-Yusufiah Sidorejo. The research used a quasi-experimental design with a pretest-posttest control group design and was carried out over four meetings. The participants consisted of two classes: the experimental class, which received instruction using the NHT model, and the control class, which was taught using conventional methods. Data were collected through tests, observations, and questionnaires, and analyzed using a t-test to determine differences between groups. The results showed a significant improvement in the experimental group’s performance, with a posttest mean score of 83.6 compared to 72.1 in the control group, and a Sig. (2-tailed) value of 0.001 (p < 0.05). Observation data also indicated that students in the experimental class were more active, collaborative, and engaged in the learning process. Based on these findings, it can be concluded that the NHT cooperative learning model effectively enhances students’ writing performance, participation, and motivation in learning procedural texts.